Do applicants from Generation X, Y, Z differ in personality traits? data from selection procedures in aviation (1987–2019) - Stelling, Dirk (Frontiers in Psychology, 2023)
The objective of this study is to research personality trait differences across generations and the impact of age, gender and self-presentation on these traits. A total of 82,147 applicants (aged 17-24) for aviation training (pilot, air traffic controller), born between 1965 and 2002, were divided into three cohorts (Generation X, Y, Z). We analysed data from the Temperament Structure Scales (TSS) personality questionnaire, which was collected during selection procedures between 1987 and 2019. Generational differences were analysed by ANCOVAs with generation and gender as group factors, controlled by age and self-presentation (social desirability). Age had no significant impact, but we observed slight gender differences in emotional stability, vitality, empathy, and self-presentation across all generations. The generational differences found exhibited extremely small effect sizes, suggesting that applicants have become more extraverted, controlled (with lower aggression and higher rigidity), and inclined to present themselves in a more favourable manner. We discuss the implications of these findings for the aviation industry and the applicability of Generation theory in personality trait research.